Discretionary bonus pools, mutual monitoring, and employees’ influence activities: An experimental investigation - Elsinger, Florian (Accounting, Organizations and Society, 2026)
This study investigates the joint effects of the extent of superior discretion in bonus allocations and the degree of mutual monitoring within teams on team output and unproductive influence activities of employees. Increasing discretion granted to superiors allows them to use their private information to motivate effort. Prior literature, however, also stresses that increasing discretion induces employees to engage in unproductive activities to influence bonus allocations. Drawing on behavioral theory, I argue and show that when superiors only have narrow discretion over bonus allocations and, hence, employees have few pecuniary incentives to engage in influence activities, team output increases with higher degrees of mutual monitoring in teams. In this case, employees are better able to effectively coordinate their efforts. This positive effect of mutual monitoring, however, diminishes as superior discretion over bonus allocations increases. In this case, employees’ greater engagement in influence activities undercuts their ability to coordinate on high team output with higher degrees of monitoring. This study contributes to the literature on discretionary bonus pools by providing evidence on the joint effects of superior discretion and mutual monitoring on team outcomes and by identifying conditions under which limiting superior discretion becomes more beneficial.